Sacred Dance in Dante’s Paradiso: Mystical Prayer or Transgressive Blasphemy? - Vettori, Alessandro (Quaderni d'Italianistica)

(untitled) (Iter Press, 2024)
Dance is here viewed as a form of prayer. In the medieval controversy over the legitimacy of secular and religious dancing, Dante sides with the sacredness of moving one’s body harmoniously at the rhythm of music. Because in Paradiso prayer is no longer a request or a desire for intimacy with the divine, the heavenly souls manifest their blissful achievement of finally being with God through their glorious bodies and their voices, singing and dancing, as for example in the concentric dance of the wise souls in the Heaven of the Sun (Paradiso X, XI, and XII).